Immunoglobulin light chain mRNA detected by in situ hybridisation in diagnostic fine needle aspiration cytology specimens. Issue 9 (September 1996) - Stewart, C J; Farquharson, M A; Kerr, T; McCorriston, J
Abstract : AIMS: To demonstrate expression of immunoglobulin light chain mRNA in diagnostic fine needle aspiration (FNA) cytology specimens using an in situ hybridisation (ISH) technique; and to evaluate ISH in a series of reactive lymphoid proliferations and malignant lymphomas. METHODS: Forty diagnostic FNA specimens showing a lymphoid cell population were examined for immunoglobulin light chain mRNA expression using ISH. Aspirates were obtained from lymph node (n = 34), salivary gland (n = 3), subcutaneous tissue, thyroid and breast (n = 1 each). The cases included 20 B cell lymphomas, five cases of Hodgkin's disease and 15 reactive lymphoid proliferations. Comparison with light chain immunoreactivity was made in 36 cases and histological correlation from biopsy material was available in 24. RESULTS: Immunoglobulin light chain restriction was demonstrated in 14 of 20 B cell lymphomas using ISH and in six of 17 B cell lymphomas using immunocytochemistry. A polytypic pattern of light chain expression was observed in four of five cases of Hodgkin's disease with both techniques, and in 12 of 15 and 11 of 14 reactive lymphoid proliferations using ISH and immunocytochemistry, respectively. CONCLUSIONS: The assessment of immunoglobulin light chain expression is a useful adjunct to morphology in the diagnosis of reactive and malignant lymphoid proliferations in FNA specimens. Light chain restriction can be shown using either immunocytochemistry or ISH, but the latter is more sensitive in the diagnosis of B cell lymphoma.